EDUKASI PENTINGNYA MENUMBUHKAN JIWA ENTERPRENEUR BAGI SISWA SMKN 1 SERI KUALA LOBAM - Ciptha, Andrea; Fadillah, Muhammad Rizky; Marhani, Rizky Intan; Sari, Sevia Permata; Nuraliza, Siti; Supiati, Supiati (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
Motivation, support and high desire are very necessary to start a business. So entrepreneur must be known as soon as possible to Indonesian citizens. Introduction to learning entrepreneur through educational activities entrepreneurin Bintan Regency, to be precise at SMKN 1 Seri Kuala Lobam in Kuala Sempang Village. The aim of this education is to prepare students to generate employment opportunities, alleviate the problems of unemployment, poverty and economic downturn. There are targets and outcomes that are the aim of educational programs entrepreneur motivatingly, creatively and skillfully in providing information to SMKN 1 Seri Kuala Lobam about the importance of understanding education entrepreneur motivating and creative and can instill the soul entrepreneur to students from an early age. The method used in this education is to use observation to dig up information regarding the condition of students at SMKN 1 Seri Kuala Lobam Kuala Sempang Village and socialization to take part in a series of socialization activities to foster an entrepreneurial spirit. The results of this training are the outcomes of carrying out several educational activities, including a tendency to grow in motivation regarding persistence to awaken the soul. Entrepreneur for student. The emergence of a strong awareness of the importance of entrepreneurship from generation to generation starting at a young age who emulate the successful behavior of entrepreneurs who have been running and are successful. In the end, by carrying out this activity the participants are expected to gain scientific insight in the field of entrepreneurship so that they can improve their souls entrepreneur million to raise the enthusiasm of the younger generation for entrepreneurship. The conclusion from this activity is that it is able to foster motivation and a sense of enthusiasm, awakening the soul entrepreneur among students of SMKN 1 Seri Kuala Lobam. Apart from that, the benefits of this activity can increase strong awareness of the importance of entrepreneurship starting from a young age. In the formation of the soul entrepreneur The students of SMKN 1 Seri Kuala Lobam are given education by providing motivation to improve the formation of the soul entrepreneur.